COUNSELING STUDENTS WORK VALUES - Mehmet BİLGİN (International Journal of Eurasia Social Sciences, 2015)
Work values or work goals play a crucial role in peoples’ lives and career development as these can affect not only the choice of education and career but also the person’s commitment to learning and work. People tend to select careers that are consistent with their work values, or they change their work values to suit the dominant values in their chosen employment field. Work values have been defined not only as desired outcomes or behaviors in the work environment but also as positive job satisfaction reinforcement. The aim of this study was to identify the work values of counseling students at the undergraduate level. The participants were 439 undergraduate students. Super’s Work Values Inventory–Revised was used in the study. The results show that students feel their most important work values are lifestyle, achievement, and independence. Male and female students expressed their most important values as Lifestyle, Success, and Independence. In addition, female students stated that they cared about the Variety and Workplace values. In contrast, male students stated that they cared about the Prestige and Coworkers values. In addition, for the co-workers value there were significant differences between the first and fourth undergraduate students.